Frequent intrathecal production of antibodies to the viral capsid antigen of Epstein-Barr virus in patients with central nervous system post-transplant lymphoproliferative disorder - Otto, Carolin; Radbruch, Helena; Wilken, Diana; Lietzow, Tatjana; Steinhagen, Katja; Grage-Griebenow, Evelin; von Brünneck, Ann-Christin; Jarius, Sven; Hofmann, Jörg; Pache, Florence; Ruprecht, Klemens (Journal of neuroimmunology, 2022)
Primary central nervous system post-transplant lymphoproliferative disorder (PCNS-PTLD) is strongly associated with Epstein-Barr virus (EBV). We analysed intrathecal production of EBV viral capsid antigen (VCA) immunoglobulin (Ig)G and IgA and Epstein-Barr nuclear antigen-1 (EBNA-1) IgG in nine patients with PNCS-PTLD and 20 patients with non-inflammatory neurological diseases (NINDs). Intrathecally produced VCA-IgG was detected in 7/9 (78%), VCA-IgA in 6/9 (67%) and EBNA-1-IgG in 2/9 (22%) patients with PCNS-PTLD, but not in NINDs. This exploratory study suggests that intrathecal EBV antibody production might be frequent in PCNS-PTLD. Detecting intrathecally produced VCA-IgG and VCA-IgA could thus potentially be helpful for diagnosing PCNS-PTLD.
Gesehen am 25.08.2022